Effect of plyometric exercise training on vertical jump height between ground and sand surface in Male volleyball players - T.N.SURESH,; JAYALAKSHMI.T,; RIZWANA BEGUM NAGOOR MEERAN,; V.P.R. SIVAKUMAR, (International Journal of Pharma and Bio Sciences, 2017)
Sport training in volleyball players should also focus on vertical jump height in consistent with demand of the sport. Since plyometrics training improves vertical jump height, it can be useful training strategy to improve the performance of volleyball players. The aim of the study is to compare the effects of Plyometric exercise training on ground versus plyometric exercise training on sand on vertical jump height in male volleyball players. Convenience samples of thirty professional volleyball players in the age of 18-25 were recruited. Intervention using plyometric training on ground and sand protocol was administered on the volley ball players. The outcome measures were assessed before the intervention and end of the first and second week. The study concludes that plyometric training on sand as a useful training strategy to improve vertical jump height in volley ball players than plyometric training on ground.